2013
DOI: 10.2174/1874255620130812001
|View full text |Cite
|
Sign up to set email alerts
|

Ovarian Stimulation with Urofollitropin (uFSH) Results in a Lower Yield of Oocytes Compared to Recombinant FSH (rFSH), Nevertheless, uFSH is at Least as Effective as rFSH in Younger Patients: Preliminary Results of a Retrospective Study with Antagonist Protocols in an IVF/ICSI Program

Abstract: Abstract:Objective: Differences in the mode of action between recombinant FSH (rFSH) and urinary derived FSH (uFSH) have been reported in cycles down-regulated by agonists. The aim of our study was to determine, if these differences also exist in cycles down-regulated by antagonists.Method: Antagonist cycles performed between 2009 -2012 were divided into two groups:1. Cycles stimulated with rFSH preparations: Follitropin alfa (n=203) and Follitropin beta (n=443) and 2. Cycles stimulated with Urofollitropin (n=… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2015
2015
2018
2018

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 47 publications
(43 reference statements)
0
2
0
Order By: Relevance
“…Several trials[ 24 25 26 27 28 29 30 ] have compared embryo and oocyte quality in patients receiving recombinant versus urinary formulations. Studies by Hedon et al .…”
Section: Ethodologymentioning
confidence: 99%
See 1 more Smart Citation
“…Several trials[ 24 25 26 27 28 29 30 ] have compared embryo and oocyte quality in patients receiving recombinant versus urinary formulations. Studies by Hedon et al .…”
Section: Ethodologymentioning
confidence: 99%
“…In another retrospective study, the quality of oocytes produced by HP uFSH was found to be better than those produced by rFSH. [ 30 ]…”
Section: Ethodologymentioning
confidence: 99%